(untitled) (Journal of Hama University, 2020)
The aim of the current research to uncover the concept of political freedom in Kant’s philosophy is to assert that Kant’s freedom is closely related to ethics and shed light on the role of political freedom for individuals in achieving peace in society. The analytical descriptive method was followed for the most important books of Kant (criticism of the practical mind), (criticism of the abstract mind) and (the project of permanent peace). And to present the most important concepts related to freedom such as virtue, truth and reason. The results of the research showed that freedom in Cantonese thought is the key to achieving peace in the society of one state and between different countries. Through virtue and proving political freedom among individuals is what the state achieves. In addition, the essence of political freedom is closely linked to the existence of a republican system in the state. and respects the law.